Lessons learned from expanded reproductive carrier screening in self‐reported Ashkenazi, Sephardi, and Mizrahi Jewish patients. Issue 2 (27th December 2019) - Akler, Gidon; Birch, Ashley H.; Schreiber‐Agus, Nicole; Cai, Xiaoqiang; Cai, Guiqing; Shi, Lisong; Yu, Chunli; Larmore, Anastasia M.; Mendiratta‐Vij, Geetu; Elkhoury, Lama; Dillon, Mitchell W.; Zhu, Jun; et al.
Abstract: Background: Next‐generation sequencing (NGS)‐based panels have gained traction as a strategy for reproductive carrier screening. Their value for screening Ashkenazi Jewish (AJ) individuals, who have benefited greatly from population‐wide targeted testing, as well as Sephardi/Mizrahi Jewish (SMJ) individuals (an underserved population), has not been fully explored. Methods: The clinical utilization by 6, 805 self‐reported Jewish individuals of an expanded NGS panel, along with several ancillary assays, was assessed retrospectively. Data were extracted for a subset of 96 diseases that, during the panel design phase, were classified as being AJ‐, SMJ‐, or pan‐Jewish/pan‐ethnic‐relevant. Results: 64.6% of individuals were identified as carriers of one or more of these 96 diseases. Over 80% of the reported variants would have been missed by following recommended AJ screening guidelines. 10.7% of variants reported for AJs were in "SMJ‐relevant genes, " and 31.2% reported for SMJs were in "AJ‐relevant genes." Roughly 2.5% of individuals carried a novel, likely pathogenic variant. One in 16 linked cohort couples was identified as a carrier couple for at least one of these 96 diseases. Conclusion: For maximal carrier identification, this study supports using expanded NGS panels for individuals of all Jewish backgrounds. This approach can better empower at‐risk couples for reproductive decision making. Abstract : This retrospective study examines a specific cohort of 6, 805 self‐reported Jewish (Ashkenazi/Sephardi/Mizrahi) patients who underwent carrier screening using NGS‐based expanded panels. Results are presented from an extracted set of 96 genes initially classified as "Jewish‐relevant, " albeit that a majority of the patients (79% of cohort) opted for much larger panels that contained this set of 96. The findings highlight the value of large, universal sequence‐based panels, given that (a) self‐reported ethnic information is often unreliable/complex, and (b) many patients want maximal information for their reproductive decision making.